Integrating product design into the supply chain. Issue 1 (31st December 2016) - Khan, Omera; Stolte, Terje; Creazza, Alessandro; Hansen, Zaza Nadja Lee
Abstract: Purpose : The aim of the research is to illustrate how companies can create competitive capabilities through integration of product design into the supply chain. In doing so the paper reveals the challenges and the opportunities that companies face when integrating product design and supply chain. Design/Methodology/Approach : The research is case based and focuses on six companies. Ten interviews were carried out in each of these with senior managers. The Resource-Based View (RBV) is utilised to put these empirical findings into a theoretical context. Findings : The findings reveal a range of opportunities and challenges when integrating product design and the supply chain and subsequently a step-by-step guide is developed to address these. Practical Implications : The research provides key recommendations to companies on how to create competitive capabilities by integrating product design into the supply chain. Originality/Value : This paper provides novel insights to both practitioners and researchers. For practitioners detailed recommendations are given on how they can maximise benefits through integrating product design into the supply chain. The RBV has been harnessed to highlight how integration needs to be balanced with the company's current resources and capabilities.